HUBUNGAN DERAJAT KEPARAHAN AKNE VULGARIS DENGAN TINGKAT KEPERCAYAAN DIRI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA AMBON - Gabriela Debora Saiya; Amanda G. Manuputty; Alessandra F. Saiya; Sherly Yakobus; Christiana R. Titaley; Rita S. Tanamal (Fakultas Kedokteran Universitas Pattimura, 2023)
Acne vulgaris is a chronic inflammation of the pilosebaceous unit with multifactorial causes and clinical manifestations in the form of comedones, papules, pustules, nodes, and cysts. According to the Global Burden of Disease (GBD) study, acne affects 85% of adolescents to young adults aged 12-25 years. Acne vulgaris has an impact both physically and psychologically, including a person's self-confidence. The purpose of this study was to determine the relationship between the severity of acne vulgaris with the level of self-confidence of the students of the Faculty of Medicine, University of Pattimura. This type of research is quantitative analytic with a cross-sectional study approach. Research respondents were students of the Faculty of Medicine, Pattimura University, Ambon with acne with a total of 83 respondents who were selected by simple random sampling technique. Characteristics of respondents based on age and gender were dominated by respondents aged 19 years (31.3%) and females (86.7%). The results showed that most of the respondents experienced mild acne as many as 54 respondents (65.1%), mostly dominated by moderate-high self-confidence as many as 55 respondents (66.3%). The results showed that there was a significant relationship between the severity of acne vulgaris and the level of confidence in the students of the Faculty of Medicine, Pattimura University, Ambon with p = 0.001. The result of this study can be used as reference material for further research on other causal factors besides acne vulgaris that affect self-confidence.